Mismeasured household size and its implications for the identification of economies of scale - Timothy J. Halliday (Institute for the Study of Labor (IZA), 2008)
We consider the possibility that demographic variables are measured with errors which arise because household surveys measure demographic structures at a point-in-time, whereas household composition evolves throughout the survey period. We construct and estimate sharp bounds on household size and find that the degree of these measurement errors is non-trivial. However, while these errors have the potential to resolve the Deaton-Paxson paradox, they fail to do so.
urn:nbn:de:101:1-2009010734
Keywords: J12; C14; 330; Migration; measurement error; semi-parametric bounds; economies of scale; Privater Haushalt; Bevölkerungsstatistik; Messung; Statistischer Fehler; USA